2015
DOI: 10.1016/s1470-2045(15)00128-x
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of mammographic screening from age 40 years on breast cancer mortality in the UK Age trial at 17 years' follow-up: a randomised controlled trial

Abstract: SummaryBackground Age-specifi c eff ects of mammographic screening, and the timing of such eff ects, are a matter of debate. The results of the UK Age trial, which compared the eff ect of invitation to annual mammographic screening from age 40 years with commencement of screening at age 50 years on breast cancer mortality, have been reported at 10 years of follow-up and showed no signifi cant diff erence in mortality between the trial groups. Here, we report the results of the UK Age trial after 17 years of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
118
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(131 citation statements)
references
References 29 publications
6
118
0
7
Order By: Relevance
“…They are also consistent with those of a major cohort evaluation of screening in this age group 12. The UK Age Trial found a smaller effect of screening in this age group that was partly due to lower participation rates and partly due to the fact that the screening in the UK Age Trial had only a transient effect on mortality from aggressive, grade 3 breast cancers 11. In the current study, on the other hand, there was a substantial effect on deaths due to grade 3 breast cancers in women younger than 50 years.…”
Section: Discussionsupporting
confidence: 85%
“…They are also consistent with those of a major cohort evaluation of screening in this age group 12. The UK Age Trial found a smaller effect of screening in this age group that was partly due to lower participation rates and partly due to the fact that the screening in the UK Age Trial had only a transient effect on mortality from aggressive, grade 3 breast cancers 11. In the current study, on the other hand, there was a substantial effect on deaths due to grade 3 breast cancers in women younger than 50 years.…”
Section: Discussionsupporting
confidence: 85%
“…The authors also found no evidence for increased overdiagnosis in that age group. 33 For older women, the decision to screen is more complicated. ACS guidelines recommend annual screening only if older women have life expectancy of at least 5 years and only if they are in generally good health, with no significant comorbid conditions; thus, there are no data to indicate whether, or at what frequency, screening in older women is or is not supported by ACS guidelines.…”
Section: Overdiagnosis and Agementioning
confidence: 99%
“…Breast cancer (currently considered a heterogeneous disease) mortality decreased significantly over the past three decades worldwide [25][26][27][28] due to early detection [29][30][31][32] and adjuvant systemic therapy (AST) [32,33]. However the risk of recurrence is still high and dependent upon numerous factors including tumor size, involvement of regional lymph nodes, histologic grade, expression of hormone receptors (estrogen and progesterone), and human epidermal growth factor receptor 2 (HER2) amplification.…”
Section: Discussionmentioning
confidence: 99%